Pemodelan Dan Simulasi Penyebaran Penyakit Covid-19 Dengan Menggunakan Model Cellular Automata - Vira Chlaudia Makahinda; Gladly Caren Rorimpandey; CIndy Pamela Munaiseche (Program Studi Teknik Informatika, 2022)
The covid-19 is a virus that is currently plaguing the world by a highly unexpected form of infection. The covid-19 virus infection itself has grown remarkably fast not only in Indonesia but worldwide. Even its spread can be spread quickly and people are vulnerable to the virus. Based on data obtained from the spread of Sitaro health services, the number of covid19 cases in Sitaro district from April to June was 139 with 10 dead and 116 with a recovery from covid-19. In the case of covid19, there is a dire need for cooperation from all good people of the general public, health and government efforts to be together-together prevent further spread of covid-19 in our area. At current research the author USES the cellular model in simulation making. The cellular automata model was first introduced by Jhon Von Neuman and Stain Slaw Marchin Ulam in 1948 with the cellular space name that was a simple model for studying the behavior of a large complex system and learning biological processes. Cellular automata in this study was also used to predict the covid-19 spread spread in the coming month.